Design, mechanism, delivery and therapeutics of canonical and Dicer-substrate siRNA - Maria Abdul Ghafoor Raja; Haliza Katas; Muhammad Wahab Amjad (Elsevier, 2019)
Upon the discovery of RNA interference (RNAi), canonical small interfering RNA (siRNA) has been recognized to trigger sequence-specific gene silencing. Despite the benefits of siRNAs as potential new drugs, there are obstacles still to be overcome, including off-target effects and immune stimulation. More recently, Dicer substrate siRNA (DsiRNA) has been introduced as an alternative to siRNA. Similarly, it also is proving to be potent and target-specific, while rendering less immune stimulation. DsiRNA is 25-30 nucleotides in length, and is further cleaved and processed by the Dicer enzyme. As with siRNA, it is crucial to design and develop a stable, safe, and efficient system for the delivery of DsiRNA into the cytoplasm of targeted cells. Several polymeric nanoparticle systems have been well established to load DsiRNA for in vitro and in vivo delivery, thereby overcoming a major hurdle in the therapeutic uses of DsiRNA. The present review focuses on a comparison of siRNA and DsiRNA on the basis of their design, mechanism, in vitro and in vivo delivery, and therapeutics. Keywords: RNA interference, Drug delivery system, Polymeric nanoparticles, Gene silencing, Gene carrier, Non-viral vector